Social and Economic Impact of the Six Universities Initiative Japan-Indonesia Program on Sustainable Development: JEL Classification: I30, O15, O19, Q56, R58 - Koichi, Ohashi; Tamma, Sukri; Ibrahim, Muhammad Akmal; Hasniati, Hasniati (Newinera Publisher, 2025)
This study explores the impact of the Six Universities Initiative Japan-Indonesia (SUIJI) Program on sustainable development in rural South Sulawesi, Indonesia. The program aims to foster community-based social innovation through cross-cultural collaboration between Japanese and Indonesian students, who engage directly with local communities to address environmental, social, and economic challenges. The study uses a qualitative approach, including participant observation, in-depth interviews, and document analysis, to assess the program's impact in four locations: Barrang Lompo Island, Lakkang Island, Toraja, and Polewali Mandar. Key findings indicate that the program significantly improved agricultural productivity, environmental sustainability, and community well-being through the introduction of organic farming techniques, sustainable fisheries practices, and improved education. Students participating in the program developed cross-cultural communication skills and practical experience in applying theoretical knowledge in real-world contexts. However, challenges related to cultural differences, language barriers, and limited infrastructure hindered the program's full potential. The study concludes that while the SUIJI Program had a positive impact on rural development, its long-term sustainability depends on stakeholder support and improved infrastructure. This study contributes to broader discussions on social innovation and sustainable development, emphasizing the importance of integrating global and local perspectives. Further research is needed to explore the long-term adaptability of communities to introduced innovations and the role of infrastructure in supporting sustainable development in rural areas.